1992
DOI: 10.1212/wnl.42.10.1894
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease in twins studied with 18 F‐dopa and positron emission tomography

Abstract: We used 18F-dopa PET to examine concordance for dysfunction of the nigrostriatal dopaminergic system in 18 co-twins of patients with Parkinson's disease (PD) and scanned one clinically concordant monozygotic (MZ) twin pair, 17 asymptomatic co-twins (10 MZ, 7 dizygotic [DZ]), and 13 twins with PD (8 MZ, 5 DZ). Mean 18F-dopa uptake of the twins with PD was significantly reduced in putamen to 38% and in caudate to 66% of normal. Mean putamen 18F-dopa uptake for the 17 asymptomatic co-twins was also significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(64 citation statements)
references
References 0 publications
2
61
0
1
Order By: Relevance
“…A genetic contribution to Parkinson's disease (PD) is well recognized [1][2][3] with B10% of the cases carrying mutations that lead to rare Mendelian forms of the disease. 4 Recently, independent genomewide association studies (GWAS) established an unequivocal role for common genetic variants in the etiology of PD [5][6][7][8][9][10][11] and suggested a population-specific genetic heterogeneity, with SNCA, PARK16, BST1 and LRRK2 as shared risk loci for PD, [6][7][8]10,11 and MAPT as an European-specific risk locus.…”
Section: Introductionmentioning
confidence: 99%
“…A genetic contribution to Parkinson's disease (PD) is well recognized [1][2][3] with B10% of the cases carrying mutations that lead to rare Mendelian forms of the disease. 4 Recently, independent genomewide association studies (GWAS) established an unequivocal role for common genetic variants in the etiology of PD [5][6][7][8][9][10][11] and suggested a population-specific genetic heterogeneity, with SNCA, PARK16, BST1 and LRRK2 as shared risk loci for PD, [6][7][8]10,11 and MAPT as an European-specific risk locus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using positron emission tomography (PET) scanning have demonstrated that the onset of PD symptoms is preceded by a period -estimated at five to six years on average -of impaired dopaminergic function in the striatum [121]. When the procedure was applied in a twin study to assess nigrostriatal dysfunction instead of clinically diagnosed PD, concordance rates were 45% in monozygotic twins versus 29% in dizygotic twins [122].…”
mentioning
confidence: 99%
“…It is known that PD does not generally show hereditary characteristics but some cases have shown clear autosomic dominant transmission with reduced penetrance 14 . Identical twin studies have shown low PD concordance 19 , although PET scan studies on twins using fluorodopa demonstrated that the non-parkinsonian twins have a greater tendency towards nigral dysfunction 3 . Barbeau et al 1 were the first to call attention to the possibility that a combination of genetic and environmental factors may be responsible for the origin of the disease.…”
Section: Discussionmentioning
confidence: 99%